The linguistic experience and its relation to coordinative thinking among students of the technological university - Dr. Abdullah Ghaith Nefal (Journal of College of Education, 2025)
The current research aims to identify the relationship between linguistic proficiency and coordinating thinking among students at the Technological University. The descriptive method was used in conducting the study, with a sample size of 188 male and female students from the first stage for the academic year 2024-2025 in Baghdad. To verify the three objectives of the research, the researcher designed a test for linguistic proficiency and adopted a test for coordinating thinking. After completing the preliminary procedures of survey and statistical analysis, the researcher applied both tools to the sample. Appropriate statistical treatments were employed, and the results of the first objective showed a statistically significant difference in the students' scores in the linguistic proficiency test, indicating that the sample possesses a good level of linguistic proficiency. The results of the second objective disclosed a statistically significant difference in scores of the coordinating thinking, showing that the sample has an acceptable level of coordinating thinking. Regarding the third objective, the researcher relied on Pearson's correlation coefficient between the scores of linguistic proficiency and coordinating thinking, which was found to be (0.537). To determine the significance of the relationship, the t-value was extracted at (8.678), which is greater than the tabulated value of (1.96) at a significance level of (0.05). These results confirm a significant correlation between linguistic proficiency and coordinating thinking among the sample.     the researcher recommended adopting a linguistic proficiency approach in teaching and providing students with areas of coordinating thinking, and suggested conducting a study at the secondary stage.
Keywords: linguistic experience, coordinative thinking